Assessment of Neurotoxic Pesticides Residues in Fruits and Vegetables by Bioassay Technique - Bohara, Khagendra; Bhatt, Love Raj; Saud, Prem; Joshi, Mahesh Kumar (Journal of Nepal Chemical Society, 2022)
A study was performed to investigate the status of organophosphate and carbamate pesticide residues present in fruits and vegetables. For this purpose, samples were collected from the local markets of Godawari municipality and Dhangadhisub-metropolitan city of Sudurpaschim province in the Kailali district of Nepal. Samples were analyzed for pesticide residues by the rapid bioassay for pesticide residues (RBPR) technology. The obtained results showed that in fruits the highest inhibition (%) of carbamates(CMs) was present in the banana 29.488%and the highest inhibition (%) of organophosphates(OPs) was present in orange 17.433%. The highest acetylcholinesterase (AChE) inhibition (%) of CMs and OPs pesticides was found to be associated with Sting gourd i.e. 20.574% and 25.357% respectively. The findings point out the urgent need to address the potential risk of exposure to multiple pesticide residues via stringent monitoring programs on daily basis from pesticides present in the diet.